Plum Tree Gums as Local Alternatives for Foreign Drilling Fluid Materials - Almahdawi, Faleh H. M.; Hussain, Mohammad N.; Jasim, Haider Salim (Journal of Petroleum Research and Studies, 2017)
A few years ago oil well drilling cost increased due to using modern technique such as equipment and materials that are used by specialist companies so studies and researches were required to decrease these costs. In this study we tried to find local alternatives for foreign drilling fluid materials that are aimed to decrease oil well drilling cost although the cost of drilling fluid materials reach to 30 % of total materials cost of drilling oil well. In the first part of this study seven local materials and it's tested under API Specification 13A for Drilling Fluids Materials were investigated. Plum Tree Gum was succeeded in this test among several other materials as drilling fluid materials. The second part of this study was a comparison between these local alternative and similar foreign materials for same sample to show physical and rheological properties. The third part of this study was tested this local alternative under different values temperature to show effect the temperature on physical and rheological properties of this local alternative. The results approved that; Plum Tree Gum, local alternative, can use as filtration control materials for water based drilling fluid. Also this local alternative increased viscosity as minimal for water based drilling fluids, So it can be used as part alternative for Bentonite to increase viscosity by increasing Yield point and decreasing solids concentration in drilling fluids so it has positive effect on Rig equipment’s and Pay-zone. Plum Tree Gum is Ore polymers (plant origin)